AN AUTEUR OF DECADENCE: SOFIA COPPOLA AND THE UNBEARABLE HEAVINESS OF COMING OF AGE - Majestya, Nayla (Capture : Jurnal Seni Media Rekam, 2021)
As a filmmaker, Sofia Coppola is often under critiques considering her visual excess frivolous. This article is an auteur study towards the thematic and stylistic tendencies of Sofia Coppola’s films. Through analysis of her mise-en-scene, I contend that Coppola, as a film auteur,  tends to glorify the image of the lost generation. This glorification is bolstered by her signature style that echoes the spirit of the Decadent movement in the late-nineteenth-century European art scenes, which was preoccupied with the idea of fin de siècle or society in transition at the end of time. This idea is exemplified most vividly by motifs such as hedonistic behavior, visual excess, and cultural decline.